Bridging Knowledge and Action: Understanding the Link between Sustainability Awareness and Consumption Habits among Lithuanian and Polish Students - Bartkute , Rasa; Griesiene, Ingrida; Grikietyte Cebataviciene, Jurga; Skeruviene, Vitalija; Wojtyra, Joanna (Transformations In Business & Economics, 2026)
This article examines sustainable consumption in the context of the Agenda 2030 Sustainable Development Goals (SDGs), with particular emphasis on Goal 12 related to sustainable consumption and production. The study aims to analyse the relationship between students’ awareness of sustainability and their actual consumption choices. Unlike much of the research that frames sustainable consumption primarily in a marketing context, this paper focuses on behavioural aspects of consumption. An empirical survey was conducted among 777 university students in Lithuania (n = 477) and Poland (n = 300). The questionnaire included 41 closed-ended statements grouped into five constructs: knowledge of sustainability, sustainable attitudes, sustainable behaviour, sustainable motivation for buying food, and sustainable motivation for buying clothes. Respondents rated the statements on a 5-point Likert scale. Data were analysed using descriptive statistics, reliability testing (Cronbach’s α), normalisation, and Spearman’s correlation analysis. The findings indicate that Polish respondents scored higher than Lithuanian respondents in knowledge, attitudes, and sustainable behaviour. Nevertheless, in both countries, sustainable motivation is weaker when making actual purchase decisions, particularly regarding clothing. Statistically significant moderate correlations were found between knowledge, attitudes, and behaviour, as well as between sustainable motivation to buy food and clothing. Interestingly, no correlation was observed between monthly income and sustainable motivations. The study highlights the gap between sustainability awareness and actual consumer practices. These results underline the importance of educational and policy initiatives that not only raise awareness but also translate it into concrete behavioural changes.